Atypical progeroid syndrome (p.E262K LMNA mutation): a rare cause of short stature and osteoporosis. (14th April 2021) - Yukina, Marina; Nuralieva, Nurana; Sorkina, Ekaterina; Troshina, Ekaterina; Tiulpakov, Anatoly; Belaya, Zhanna; Melnichenko, Galina
Abstract : Summary: Lamin A/C ( LMNA ) gene mutations cause a heterogeneous group of progeroid disorders, including Hutchinson–Gilford progeria syndrome, mandibuloacral dysplasia, atypical progeroid syndrome (APS) and generalized lipodystrophy-associated progeroid syndrome (GLPS). All of those syndromes are associated with some progeroid features, lipodystrophy and metabolic complications but vary differently depending on a particular mutation and even patients carrying the same gene variant are known to have clinical heterogeneity. We report a new 30-year-old female patient from Russia with an APS and generalized lipodystrophy (GL) due to the heterozygous de novo LMNA p.E262K mutation and compare her clinical and metabolic features to those of other described patients with APS. Despite many health issues, short stature, skeletal problems, GL and late diagnosis of APS, our patient seems to be relatively metabolically healthy for her age when compared to previously described patients with APS. Learning points: Atypical progeroid syndromes (APS) are rare and heterogenic with different age of onset and degree of metabolic disorders, which makes this diagnosis very challenging for clinicians and may be missed until the adulthood. The clinical picture of the APS depends on a particular mutation in the LMNA gene, but may vary even between the patients with the same mutation. The APS due to a heterozygous LMNA p.E262K mutation, which we report in this patient, seems to have association with the generalized lipodystrophy, short stature and osteoporosis, but otherwise, it seems to cause relatively mild metabolic complications by the age of 30. The patients with APS and lipodystrophy syndromes require a personalized and multidisciplinary approach, and so they should be referred to highly specialized reference-centres for diagnostics and treatment as early as possible. Because of the high heterogeneity of such a rare disease as APS, every patient's description is noteworthy for a better understanding of this challenging syndrome, including the analysis of genotype-phenotype correlations.